2011
DOI: 10.1136/bmj.d5154
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adenoidectomy in children with recurrent upper respiratory tract infections: open randomised controlled trial

Abstract: Objective To assess the effectiveness of adenoidectomy in children with recurrent upper respiratory tract infections.Design Open randomised controlled trial.Setting 11 general hospitals and two academic centres.Participants 111 children aged 1-6 with recurrent upper respiratory tract infections selected for adenoidectomy.Intervention A strategy of immediate adenoidectomy with or without myringotomy or a strategy of initial watchful waiting.Main outcome measure Primary outcome measure: number of upper respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
0
27
0
6
Order By: Relevance
“…4,5 In a recent randomized controlled trial, we compared 2 common clinical strategies in children with recurrent URTIs: immediate adenoidectomy vs initial watchful waiting. 6 We found no relevant differences between both strategies in the incidence of URTIs and middle ear problems or health-related quality of life. We concluded that immediate adenoidectomy confers no clinical benefits over an initial watchful waiting strategy.…”
mentioning
confidence: 52%
“…4,5 In a recent randomized controlled trial, we compared 2 common clinical strategies in children with recurrent URTIs: immediate adenoidectomy vs initial watchful waiting. 6 We found no relevant differences between both strategies in the incidence of URTIs and middle ear problems or health-related quality of life. We concluded that immediate adenoidectomy confers no clinical benefits over an initial watchful waiting strategy.…”
mentioning
confidence: 52%
“…Obere Atemwegsobstruktion, rezidivierende Infekte der oberen Atemwege und sekundäre Mittelohrerkrankungen wegen adenoider Vegetation sind die klassischen Indikationen zur AT [ 62 ] . Paukenergüsse und Hörvermögen lassen sich durch die AT positiv beeinfl ussen, die Häufi gkeit von rezidivierender akuter Otitis media jedoch nicht [ 104 ] . In einer prospektiven multizentrischen Untersuchung ließ sich jedoch auch kein positiver Eff ekt der AT auf die Häufi gkeit wiederkehrender Infektionen des obe- Tab.…”
Section: Ergebnisseunclassified
“…Because of the inconsistent evidence, NICE restricted its recommendation of adenoidectomy to children with co‐present severe or persistent upper respiratory tract infection. However, a recent trial has shown that these are themselves not indications for adenoidectomy 6 …”
mentioning
confidence: 99%